2009
DOI: 10.1080/13607860802636230
|View full text |Cite
|
Sign up to set email alerts
|

Depression literacy among Chinese stroke survivors

Abstract: Low mental health literacy among older patients indicated that much more work needs to be done in health promotion and education on depression literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…One study reported that the majority of older participants (Asian immigrants residing in Canada) exhibited limited awareness of the nature and extent of mental disorders among older adults . Other studies from diverse elderly populations reported that participants commonly exhibited familiarity with mental illness symptoms, although they also reported a lack of recognition of the overall mental syndrome . In other words, older adults, regardless of their ethnic identity, are often unable to label mental disorders symptoms as mental illness.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study reported that the majority of older participants (Asian immigrants residing in Canada) exhibited limited awareness of the nature and extent of mental disorders among older adults . Other studies from diverse elderly populations reported that participants commonly exhibited familiarity with mental illness symptoms, although they also reported a lack of recognition of the overall mental syndrome . In other words, older adults, regardless of their ethnic identity, are often unable to label mental disorders symptoms as mental illness.…”
Section: Resultsmentioning
confidence: 99%
“… Mental illness as a (non)‐medical condition . Most of the qualitative studies focusing on depression reported that older participants do not consider depression to be a disease . Two studies similarly reported that a majority of participants did not view dementia as a disease .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations